Anti-platelet and anti-coagulant therapy in peripheral arterial disease prior to surgical intervention. (June 2019) - Harky, Amer; Maskell, Perry; Burgess, Mika
Objective: Peripheral artery disease is a major clinical co-morbidity that can significantly affect quality of life, especially in the presence of diabetes mellitus and older age. The focus of this literature review is on medical management, through anti-platelet and anti-coagulation, of peripheral artery disease prior to undergoing surgical or endovascular management. Method: Extensive electronic literature search performed in four major databases (PubMed, SCOPUD, Embase and Ovid) to identify the published randomized and non-randomized studies that compared and discussed the management of peripheral artery disease with different anti-thrombotic agents. Results: A total of 17 studies were identified to meet the inclusion criteria of this review. Among them, 4 were systematic review and meta-analyses, 1 was observational study and 12 were randomized controlled trials. The reported outcomes in each study are summarized and reported separately within this review. Conclusion: Peripheral artery disease is a complex and multifactorial clinical condition. The use of dual anti-platelets, such as aspirin and clopidogrel, are the key in preventing major cardiovascular events as well as stroke and death. Utilization of anti-coagulation such as direct oral anti-coagulants' as additional parameters for the prevention of disease progression, is paramount. Eventually, the choice of either dual-antiplatelet therapy or combined anti-coagulation with anti-platelets should be carefully considered, particularly following the most recent published debatable studies.